Covalent Immobilization of L-Asparaginase and Optimization of Its Enzyme Reactor for Reducing Acrylamide Formation in a Heated Food Model System - Li, Ran; Zhang, Zehua; Pei, Xiaomei; Xia, Xiaole (Frontiers in Bioengineering and Biotechnology, 2020)
Abstract: Acrylamide is a potent carcinogen and neurotoxin that is mainly formed by the Maillard reaction of asparagine with starch at high temperatures. In this work, a food safety immobilization system for L-asparaginase consisting of food-grade agarose spheres and N-hydroxysuccinimide esters was developed to decrease the formation of acrylamide in a fluid food model system. L-asparaginase was successfully immobilized with a maximum immobilization efficiency of 68.43%. The immobilized enzymes exhibited superior storage stability and reusability with 93.21% and 72.25% of the initial activity retained after 6 consecutive cycles and storage for 28 days, indicating its high industrial application potential. Meanwhile, a simplified mathematical model of the enzyme reactor was developed and verified with experiments, which demonstrated its auxiliary role in the design and optimization of reactors. In addition, simulated fluidized food components were continuously catalyzed in the designed packed bed reactor, achieving a reduction rate of nearly 89%.